Nanotechnology in Military Domain: Global Perspective in Context with Bangladesh Army - Rahman, Hasanur (Journal of Engineering Science, 2025)
Nanotechnology is one of the fastest-growing fields of science, playing a revolutionary role in various industries, including healthcare, transportation, communication, space technology, agriculture, environmental pollution management, and the defense sector globally. Nanotechnology is an interdisciplinary science that offers a significant beneficial impact on society as well as a huge advantage in the military industry. In recent years, cutting-edge developments in nanotechnology for defense have become an indispensable part of ensuring a country's national security. Defense sectors will remain obsolete and ineffective without the appropriate application of nanotechnology. Nanoparticles, nanorods, nanowires, and nanotubes are currently used to develop various advanced deference applications. It is currently applied in all the sectors of defense like land, naval, and air-based defense systems development. It plays a pivotal role in developing optical materials, smart ammunition, stealth technology, air defense systems, heat management, communication and surveillance, systems for command and control, innovative sensors, automation and robotics, and materials for energy storage, etc. Nanotechnology enables the development of small-sized lightweight weapons with higher efficiency and greater precision. Developed countries are significantly increasing their funding in nanotechnology research to capitalize on the opportunities for incorporating innovations in nanotechnology for the betterment of their military industries. However, Bangladesh is still in a rudimentary stage in terms of research activities to apply nanotechnology in the military sector. This review article focuses on the innovations and applications of nanotechnology in the defense sector, with a global perspective and an emphasis on Bangladesh. Journal of Engineering Science 16(1), 2025, 103-119